The clinical efficacy of anterior cervical discectomy and fusion with ROI-C device vs. plate-cage in managing traumatic central cord syndrome - Song, Dawei; Deng, Zicheng; Feng, Tao; Wang, Jinning; Liu, Yijie; Wang, Heng; Yang, Huilin; Niu, Junjie (Frontiers in Surgery, 2023)
Purpose: To assess the efficacy and complications of anterior cervical discectomy and fusion (ACDF) with ROI-C device versus conventional anterior plate and cage system (APCS) in managing acute traumatic central cord syndrome (TCCS). Methods: A total of 37 patients diagnosed with TCCS who underwent ACDF with ROI-C implant and APCS were recruited in this retrospective study from June 2012 to February 2020. Radiological parameters and clinical results were recorded and compared through follow-up time. Characteristics of patients and complications were also recorded. Results: All patients tolerated the procedure well. The average follow-up time was 25.00±7.99 months in the ROI-C group, and 21.29±7.41 months in the APCS group. The blood loss and operation time were significantly lower in the ROI-C group than in the ACCF group. Radiological parameters and clinical results were all improved postoperatively and maintained at the final follow-up. Fusion was achieved in all patients. ROI-C group had a lower incidence of postoperative dysphagia than the APCS group. Only 1 case of ALD was observed at the final follow-up in the APCS group. Conclusions: Both ROI-C device and APCS demonstrated satisfactory clinical effects and safety in managing symptomatic single-level traumatic central cord syndrome with underlying instability. Both techniques could improve and maintain cervical lordosis and disc height. ROI-C device was related to a lower incidence of postoperative dysphagia, shorter operation time, and less blood loss.